Distribution and Antibiotic Resistance Patterns of Pathogenic Bacteria in Patients With Chronic Cutaneous Wounds in China - Guan, Haonan; Dong, Wei; Lu, Yechen; Jiang, Minfei; Zhang, Di; Aobuliaximu, Yakupu; Dong, Jiaoyun; Niu, Yiwen; Liu, Yingkai; Guan, Bingjie; Tang, Jiajun; Lu, Shuliang (Frontiers in Medicine, 2021)
Objective: To analyze the distribution and antimicrobial susceptibility of pathogens in patients with chronic cutaneous wounds on a national scale. Methods: This was a retrospective study conducted using the data recorded between January 1,2018 to January1, 2020 in 195 hospitals across China. In total, data of 815 patients were finally analyzed. The data collected included patients’ general condition and information regarding local cutaneous wounds, especially microbial culture and antibiotic susceptibility tests. The analyses were performed using SPSS Version 26. Results: The study included 815 patients (290 [35.6%] females; median [interquartile range] age, 63 [50-74] years) The most common causes of chronic cutaneous wounds were diabetes (183, 22.5%), infection (178, 21.8%) and pressure (140, 17.2%). In total, 521(63.9%) samples tested yielded microbial growth, including 70 (13.4%) polymicrobial infection and 451 (86.6%) monomicrobial infection. Bates-Jensen wound assessment tool (BWAT) scores >25 and wounds that lasted for more than three months had a higher positive rate of microbial culture. BWAT scores >25 and wounds in the rump, perineum, and feet were more likely to exhibit polymicrobial infection. A total of 600 strains were isolated, of which 46.2% (277 strains) were Gram-positive bacteria, 51.3% (308 strains) were Gram-negative bacteria, and 2.5% (15 strains) were fungi. The most common bacterial isolates were Staphylococcus aureus (29.2%), Escherichia coli (11.5%), Pseudomonas aeruginosa (11.0%), Proteus mirabilis (8.0%), and Klebsiella (6.7%). The susceptibility tests showed that 116 Multidrug resistance (MDR) bacterial strains were cultured. S. aureus was more resistant to penicillin (92.0%), erythromycin (58.3%) and clindamycin (50.9%). Vancomycin was the most effective antibiotic (0% resistance) against all of the Gram-positive bacteria. In addition, E. coli was more resistant to ampicillin (68.1%), ciprofloxacin (68.1%), and levofloxacin (60.9%). The lowest resistivity of Gram-negative bacteria was found in tigecycline (3.9%) and amikacin (3.6%). Conclusion The distribution of bacteria isolated from the chronic cutaneous wounds of patients varies with the BWAT scores, causes, duration and the affected body part. Multidrug resistance is a serious health issue, and therefore antibiotics used in chronic wounds must be under strict regulation. Our findings may help clinicians in making informed decisions regarding antibiotic therapy.